Clinical and molecular characterization of a family with a dominant renin gene mutation and response to treatment with fludrocortisone - Bleyer, Anthony J.; Zivná, M.; Hulková, H.; Hodanová, K.; Vyletal, P.; Sikora, J.; Zivný, J.; Sovová, J.; Hart, T. C.; Adams, J. N.; Elleder, M.; Kapp, Katharina; et al. (International journal of radiation oncology, biology, physics, 2010)
BACKGROUND: A family was identified with autosomal dominant inheritance of anemia, polyuria, hyperuricemia, and chronic kidney disease. Mutational analysis revealed a novel heterozygous mutation c.58T > C resulting in the amino acid substitution of cysteine for arginine in the preprorenin signal sequence (p.cys20Arg) occurring in all affected members. - METHODS: Effects of the identified mutation were characterized using in vitro and in vivo studies. Affected individuals were clinically characterized before and after administration of fludrocortisone. - RESULTS: The mutation affects endoplasmic reticulum co-translational translocation and posttranslational processing, resulting in massive accumulation of non-glycosylated preprorenin in the cytoplasm. This affects expression of intra-renal RAS components and leads to ultrastructural damage of the kidney. Affected individuals suffered from anemia, hyperuricemia, decreased urinary concentrating ability, and progressive chronic kidney disease. Treatment with fludrocortisone in an affected 10-year-old child resulted in an increase in blood pressure and estimated glomerular filtration rate. - CONCLUSIONS: A novel REN gene mutation resulted in an alteration in the amino acid sequence of the renin signal sequence and caused childhood anemia, polyuria, and kidney disease. Treatment with fludrocortisone improved renal function in an affected child. Nephrologists should consider REN mutational analysis in families with autosomal dominant inheritance of chronic kidney disease, especially if they suffer from anemia, hyperuricemia, and polyuria in childhood.
Gesehen am 15.02.2023